Effectiveness of the Modified WHO Labour Care Guide to Detect Prolonged and Obstructed Labour Among Women Admitted at Eight Publicly Funded, Midwife-Led Community Health Facilities in Rural Mbarara District, Southwestern Uganda: An Ambispective Cohort Study - Mugyenyi GR; Tumuhimbise W; Atukunda EC; Tibaijuka L; Ngonzi J; Kayondo M; Kanyesigye M; Musimenta A; Yarine FT; Byamugisha JK (International Journal of Women's Health, 2025)
Godfrey R Mugyenyi,1,2 Wilson Tumuhimbise,3 Esther C Atukunda,2,4 Leevan Tibaijuka,1 Joseph Ngonzi,1 Musa Kayondo,1 Micheal Kanyesigye,2 Angella Musimenta,3 Fajardo T Yarine,1 Josaphat K Byamugisha5 1Obstetrics and Gynaecology Department, Mbarara University of Science and Technology, Mbarara, Uganda; 2Support Mom’s Project, Mbarara University of Science and Technology, Mbarara, Uganda; 3Computing and Informatics Department, Mbarara University of Science and Technology, Mbarara, Uganda; 4Pharmacy department, Mbarara University of Science and Technology, Mbarara, Uganda; 5Obstetrics and Gynaecology department, Makerere University College of Health Sciences, Kampala, UgandaCorrespondence: Godfrey R Mugyenyi, Email gmugyenyi@must.ac.ugBackground: Obstructed labour, a sequel of prolonged labour, remains a significant contributor to maternal and perinatal deaths in low resource settings.Objective: We evaluated the modified WHO labour care guide (LCG) in detecting prolonged/obstructed labour compared to the traditional partograph at publicly funded maternity centers in Southwestern Uganda.Methods: LCG was deployed to monitor labour by trained health care providers in 2023. We reviewed all patient labour monitoring records for the first quarter of 2024 (LCG-intervention) and 2023 (partograph-before LCG introduction) from eight randomized maternity centers. Our primary outcome was the proportion of women diagnosed with prolonged and or obstructed labour. Secondary outcomes included: mode of delivery, labour augmentation, stillbirths, maternal deaths, Apgar score, uterine rupture, postpartum haemorrhage and tool completion. Data was collected in REDcap and analyzed using STATA v17; statistical significance was p < 0.05.Results: A total of 991 (49.3%) and 1020 (50.7%) women were monitored using the LCG and partograph, respectively. The mean maternal and gestation ages were similar between the two groups, reported at 25.9 (SD=5.6) years, and 39.4 (SD=1.8) weeks, respectively. Overall, 120 (12.4%) cases of prolonged/obstructed labour were diagnosed (100 for LCG versus 20 for partograph); LCG had six times higher odds of diagnosing prolonged/obstructed labour compared to the partograph (aOR = 5.94;CI 95%3.63– 9.73, P < 0.001). Detection of obstructed labour alone using LCG increased 12-fold compared to the partograph (aOR = 11.74;CI 95%3.55– 38.74, P < 0.001). We observed increased Caesarean section rates (aOR=6.12;CI 95%4.32– 8.67, P < 0.001), augmentation of labour (aOR = 3.11;CI 95%1.81– 5.35, P < 0.001), Apgar Score at 5 minutes (aOR = 2.29;CI 95%1.11– 5.77, P = 0.025) and tool completion rate (aOR = 2.11;CI 95%1.08– 5.44, P < 0.001). We observed no differences in stillbirths, maternal deaths, postpartum haemorrhage and uterine rupture.Conclusion: Our data shows that LCG diagnosed more cases of prolonged and obstructed labour compared to the partograph among women delivering at rural publicly funded midwife-led facilities in Southwestern Uganda. More controlled and powered studies should evaluate the two tools in different facilities and sub-populations.Trial Registration: This trial registration was registered with clinical trials.gov number NCT05979194 on 2023-08-07, and the protocol was published by BMJ open, as 10.1136/bmjopen-2023-079216 on 15 April 2024.21 Trial registration number NCT05979194 clinical trials.gov.Keywords: modified WHO LCG, partograph, effectiveness, labour monitoring, ambispective cohort study, Uganda